2019
DOI: 10.1002/jcsm.12497
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D repletion ameliorates adipose tissue browning and muscle wasting in infantile nephropathic cystinosis‐associated cachexia

Abstract: Background Ctns−/− mice, a mouse model of infantile nephropathic cystinosis, exhibit hypermetabolism with adipose tissue browning and profound muscle wasting. Ctns−/− mice are 25(OH)D3 and 1,25(OH)2D3 insufficient. We investigated whether vitamin D repletion could ameliorate adipose tissue browning and muscle wasting in Ctns−/− mice. Methods Twelve‐month‐old Ctns−/− mice and wild‐type controls were treated with 25(OH)D3 and 1,25(OH)2D3 (75 μg/kg/day and 60 ng/kg/day, respectively) or an ethylene glycol vehicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(68 citation statements)
references
References 80 publications
(163 reference statements)
1
64
0
Order By: Relevance
“…We selected articles investigating nutrition interventions, macronutrient intake below recommended, and micronutrient deficiency. We found 26 articles: 10 clinical trials, 3,25–33 five cross‐sectional studies, 34–38 three experimental animal studies 39–41 (one of which also included a human cross‐sectional analysis 38 ), three narrative reviews, 6,42,43 two retrospective studies, 44,45 two systematic reviews or meta‐analyses, 46,47 and one questionnaire survey 48 . Within the 320 original and review articles published in 2018, 2019, and 2020 in JCSM , the 26 articles on nutrition that we found comprise approximately 8%.…”
Section: Taking a Stand: Journal Of Cachexia Sarcopenia And Muscle Nmentioning
confidence: 92%
See 1 more Smart Citation
“…We selected articles investigating nutrition interventions, macronutrient intake below recommended, and micronutrient deficiency. We found 26 articles: 10 clinical trials, 3,25–33 five cross‐sectional studies, 34–38 three experimental animal studies 39–41 (one of which also included a human cross‐sectional analysis 38 ), three narrative reviews, 6,42,43 two retrospective studies, 44,45 two systematic reviews or meta‐analyses, 46,47 and one questionnaire survey 48 . Within the 320 original and review articles published in 2018, 2019, and 2020 in JCSM , the 26 articles on nutrition that we found comprise approximately 8%.…”
Section: Taking a Stand: Journal Of Cachexia Sarcopenia And Muscle Nmentioning
confidence: 92%
“…Of the nutrition studies that we found, one explored the role of protein, 31 three explored the role of vitamin D, 26,38,39 two explored the role of several nutrients, 3,41 and one explored the role of natural product (astaxanthin) supplements 40 . Seven studies 25,27–30,32,33 investigated the effects of multimodal interventions (defined as two or more approaches) on muscle mass.…”
Section: Taking a Stand: Journal Of Cachexia Sarcopenia And Muscle Nmentioning
confidence: 99%
“…We and others have demonstrated the presence of WAT browning in CKD mice 5 amongst other animal disease models of cachexia as well as in patients with cachexia 6 9 . We also demonstrated WAT browning in a mouse model of cystinosis, a genetic cause of CKD 10 , 11 .…”
Section: Introductionmentioning
confidence: 54%
“…We also observed that CTNS (17p13), a gene that causes cystinosis, is associated with multisystem genetic disorder, wherein cysteine is accumulated in different tissues including the adipose and prostate. Strikingly, it is known that vitamin D repletion could be associated with CTNS knockout or mutated mice indicating vitamin D as a key-player in the pathogenesis of PCa ( Cheung et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%